COMBINATION OF INTEGRATION ANALYTIC HIERARCHY PROCESS AND GOAL PROGRAMMING FOR MULTI-OBJECTIVE OPTIMIZATION PROMOTION PROGRAM TELECOMMUNICATION SERVICES INDUSTRY - Charlitta Fhilya; Yopi Andry Lesnussa; Venn Yan Ishak Ilwaru (Barekeng)
In the globalization era, almost everyone uses the telecommunications in everyday life. The dependence on telecommunication service provider forces the service provider industry to expand the network and offer affordable promotions for all levels of the community. Based on that, â€œPT. Telkom Indonesia Tbkâ€ as one of the Indonesian companies in the telecommunication sector, must have a strategy of promotion in selling Indihome internet products.This research using the Analytic Hierarchy Process to determine weights from many promotion criteria and various alternatives, and then, using Goal Programming to find the minimum cost promotion by choosing alternatives based on the criteria. The result of this research is obtaining eight effective of nine existing promotional program.